The Analysis of Factors Affecting Fraud in the Government Sector - Miranda Prahadi (Green Publisher Indonesia, 2022)
Fraud is an action carried out by individuals or groups in a planned manner, resulting in annual financial reports that can harm the company or other parties. The study aimed to determine the effectiveness of internal control, organizational culture, compensation suitability, law enforcement, distributive justice, procedural justice, and organizational commitment to fraud with unethical behavior as a mediation variable in the community health center in Mempawah Regency. The samples of this study was the employees of the community health center in Mempawah Regency included in certain criteria with 98 respondents. The data used in this research was the primary data obtained using structured questionnaires. The data were analyzed with the approach of Structural Equation Model (SEM) using Partial Least Square (PLS). The results showed that the effectiveness of internal control, procedural justice, and organizational commitment affected the fraud. Organizational culture, compensation suitability, law enforcement, and distributive justice did not affect the fraud. Organizational culture and compensation suitability affected the unethical behavior. The effectiveness of internal control, law enforcement, distributive justice, procedural justice and organizational commitment did not affected the unethical behavior. Moreover, unethical behavior effected the fraud. This shows that the more influential the effectiveness of internal control in an agency, the lower the level of fraud occurs. Organizational culture has no effect on the occurrence of fraud at the Mempawah District Health Center.